2012
DOI: 10.5539/elt.v5n3p3
|View full text |Cite
|
Sign up to set email alerts
|

Feedback on the Feedback: Sociocultural Interpretation of Saudi ESL Learners’ Opinions about Writing Feedback

Abstract: This qualitative study employed informal conversational interviews and semi-structured individual interviews to capture the Saudi students' opinions about the feedback they receive, and about their perceptions on what constitutes helpful feedback. Sociocultural theory was used as the framework of this study. The findings suggest that the Saudi students do not think highly of the feedback, and that the feedback they desire is markedly different from what they receive. The students mentioned several impediments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 77 publications
3
28
1
Order By: Relevance
“…Similar to previous findings (Ferris, 2010;Mustafa, 2012;McMartin-Miller, 2014), students in the current study revealed a great concern about accurate writing and cared about having their written errors corrected. Students from all groups highly appreciated the type of feedback received from the researcher and were very positive about the benefits of corrective feedback.…”
Section: Rq3: Students' Expectations and Preferences For The Feedbacksupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to previous findings (Ferris, 2010;Mustafa, 2012;McMartin-Miller, 2014), students in the current study revealed a great concern about accurate writing and cared about having their written errors corrected. Students from all groups highly appreciated the type of feedback received from the researcher and were very positive about the benefits of corrective feedback.…”
Section: Rq3: Students' Expectations and Preferences For The Feedbacksupporting
confidence: 88%
“…Scholars have yet to address whether corrective feedback is effective in helping learners to eliminate errors in new pieces of writing. In addition, though abundant literature examines how teachers should balance different types of corrective feedback, learners' perspectives are also an ignored area in investigations of the effectiveness of CF (Ferris & Roberts, 2001;Mustafa, 2012). Another frequently mentioned issue in previous research is that few studies are empirically conducted on a comprehensive identification of all the error types in EFL learners' production of writing.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have examined learners' preferences in the context of EFL across cultures and ages, demonstrating the importance of students' preferences in the learning process. Additionally, several studies have revealed differences between teachers' and learners' preferences regarding CF, which may explain why Saudi EFL learners receive CF that contradicts their preferences and thus might hinder improvements in their writing performance (Mustafa, 2012).…”
Section: Saudi Learners' Preferencesmentioning
confidence: 99%
“…However, some researchers opposed the value of written feedback and claimed that it produces negative results, makes students feel stressed and anxious, and increases negative attitudes towards writing. This may be due to cultural factors and perceptions towards corrective written feedback (Rami, 2012). also points out that peer-assessment is effective in developing students' ability of objective judgments and self-assessment when they evaluate their own work.…”
Section: Methods Of Feedbackmentioning
confidence: 99%